Strange tales of an Oriental idol: an anthology of early European portrayals of the Buddha - Lopez, Donald S., Jr. (Buddhism and modernity, 2016)
We tend to think that the Buddha has always been seen as the compassionate sage admired around the world today, but until the nineteenth century, Europeans often regarded him as a nefarious figure, an idol worshipped by the pagans of the Orient. Donald S. Lopez Jr. offers here a rich sourcebook of European fantasies about the Buddha drawn from the works of dozens of authors over fifteen hundred years, including Clement of Alexandria, Marco Polo, St. Francis Xavier, Voltaire, and Sir William Jones. Featuring writings by soldiers, adventurers, merchants, missionaries, theologians, and colonial officers, this volume contains a wide range of portraits of the Buddha. The descriptions are rarely flattering, as all manner of reports some accurate, some inaccurate, and some garbled came to circulate among European savants and eccentrics, many of whom were famous in their day but are long forgotten in ours. Taken together, these accounts present a fascinating picture, not only of the Buddha as he was understood and misunderstood for centuries, but also of his portrayers